Intertextuality with the Qur’an in the Poetry of Shuaib Al-GhouthAbiMadin Al-Tilmisani (d. 594 AH) - Al-Juhani, Ahmed Dakhil Muhammad (Arts for Linguistic & Literary Studies, 2024)
This study explores the incorporation of Qur'anicintertextuality in the poetry of Shuaib Al-GhouthAbiMadin Al-Tilmisani (d. 594 AH), aiming to elucidate the associated dimensions. It relies on the poetic collection of Shuaib Al-GhouthAbiMadin Al-Tilmisani, compiled and prepared by Abdul Qadir Saud and Suleiman Al-Qurashi, where the poet employs both direct and indirect intertextuality. Direct intertextuality is evident, while indirect intertextuality serves his poetic objectives by intersecting his verses with those of the Qur'an in structure, meaning, and rhythm. Intertextuality serves as the primary methodological approach in this research, which comprises an introduction, a clarification of intertextuality's linguistic and terminological concepts, two main sections (direct and indirect/suggestive intertextuality), and a conclusion. The study finds that the poet employs Qur'anic verses directly at times, making his intertextuality explicit, while at other times, he hints at them, prompting readers to carefully discern the poetic text and its Qur'anic counterparts. The study recognizes the Qur'an's profound linguistic, intellectual, and spiritual significance, which greatly influences Arab and Islamic culture.